Influence of the Rubber Seed Type and Altitude on Characteristic of Seed, Oil and Biodiesel - Salni Salni; Poedji Loekitowati Hariani; Hanifa Marisa Hanifa (International Journal of Renewable Energy Development, 2017)
This research studies the influence of the type of rubber seed that is superior and local, altitude plant in South Sumatra province to the characteristic of seed, oil and biodiesel (methyl ester). Rubber plants planted from local rubber seed by seeds seedlings and superior rubber seed by selected clones. In the study, rubber plants planted at a different altitude, namely in Banyuasin district (18 m above sea level), Prabumulih District (176 m above sea level) and Lahat District (627 m above sea level). The results showed that the weight of the flour, the water content and ash content in the local rubber seeds larger than the superior rubber seed for all altitude, but oil content a large in the superior rubber seeds. The major of fatty acids in the rubber seed oil in all types and altitude are a linoleic acid with a different percentage except local rubber seed oil from Lahat district with the large percentage of octadecanoic acid. Free fatty acids in the oil from the superior seeds rubber of 13.897-15.494 % large than local rubber seed oil was found 9.786-10.399 % for all altitude. By esterification process using sulfuric acid catalyst, Free Fatty Acid (FFA) can be reduced to ≤ 2 %. The methyl ester made from the transesterification process of rubber seed oil after esterification using methanol and sodium hydroxide as catalyst. Analysis of methyl esters includes cetane index, flash point, kinematic viscosity, carbon residue, density, moisture content, water and sediment content and distillation compared with SNI 7182 and ASTM 6751-02.  The result indicated that the quality of methyl ester from superior rubber seed oil in the Banyuasin and Prabumulih district better than another methyl ester. The types of rubber seed altitude affect the characteristics of the seed, oil and methyl ester  but the altitude are not significantly different.Keywords: rubber seed, type, altitude, oil, biodieselArticle History: Received March 21st 2017; Received in revised form May 5th 2017; Accepted June 2nd 2017; Available onlineHow to Cite This Article: Salni, S, Hariani, P.L. and Marisa, H. (2017) Influence the Rubber Seed Type and Altitude on Characteristic of Seed, Oil and Biodiesel. International Journal of Renewable Energy Development, 6(2), 157-163.https://doi.org/10.14710/ijred.6.2.157-163